EFFECT OF TEMPERATURE ON DEVELOPMENT RATES AND SURVIVAL OF Aedes aegypti STRAIN VCRU MOSQUITO AND Aedes aegypti STRAIN PANGANDARAN - TRINURONI (NIM : 10614071), GUNADI
One of the most reported climate phenomena is the increase in the average temperature of the earth's surface. These temperature changes can have a direct physiological impact on insects that act as disease vectors, such as the Aedes aegypti mosquito. In this study, observations of several physiological components were correlated with mosquito reproduction abilities such as development time, sex ratio, and body size (identified with wing length) in two different strains, VCRU strain, and Pangandaran strain. Thirty larvae from each strain were maintained in water with temperatures of 25oC, 27oC, 30oC, 33oC, 35oC, 40OC and repeated 3 times. Observations are made until all larvae reach the adult phase or when all larvae die. The rate and time of development of the larvae are determined using the frequency dependent mean. The results of the observation showed that the optimal rate of development of VCRU strains was in the temperature range of 27-30oC with a survival rate of 84% while for the Pangandaran strain the most optimal development rate was at 30oC with a survival rate of 83%. Larvae from both strains have 100% mortality at water temperatures above 33oC. Sex ratio (male: female) measurements showed the highest and lowest ratios, both strains were achieved at the same temperature as 33oC and 30oC. The highest ratio of VCRU strains is 1.25 and the lowest is 0.6, while the highest Pangandaran strain ratio is 1.4 and the lowest is 0.6 at 30oC. The average wing width is in the range 2.2-3.4 mm for both strains. From the research that has been done, it can be concluded that temperature variations have more influence on the rate of development of Ae. aegypti strain VCRU and Pangandaran.